Direito à verdade e à memória: a Lei da Anistia Política e a consolidação da democracia no Brasil - Weymar, Jozimar Rodrigues (2012)
The present paper examines the restructuring of the legal system in Brazil from the politics reopening, how the transition to democracy developed and the scope of the Amnesty Law to address the issue of political repression memory in Brazil dictatorship (1964-1985). The transition to democracy imposes the affirmation of a Transitional Justice which demands the understanding of legal and social phenomena that involves the local and international justice, in defense of human rights. Brazilian Amnesty Law would be making difficult the criminal responsibility of aggressors. Recently, the Supreme Court affirmed the constitutionality of the Amnesty Law, contrary to the jurisprudence of the Inter-American Court of Human Rights of the American States Organization (ASO). The year of 1964 was marked in the Brazilian history because of the military coup that overthrew the president elected by popular vote, Joao Goulart, putting in his place a military system. This political system lasted from 1964 to 1985 and it was characterized by suppression of individual and political rights, censorship and repression and persecution to those who were opposed to the system. At the end of the system, the country already presented wear of all kinds; especially inflation and economic recession, providing opportunities to the opposite voices to grow with the emergence of new and strengthening partisans and unions. In 1984, several public personalities, associated to millions of Brazilians, organized a movement called "Direct Elections Now (Diretas Já), in support to the constitutional amendment proposed by Mr. Dante de Oliveira, who proposed free and direct elections to the presidency that year. In contrast to the popular will, the House of Representatives rejected the constitutional amendment proposed. Nevertheless, the popular movement led to the election, and a civilian president was elected, Tancredo Neves, ending the military dictatorship period in the country. It was enacted in 1988 the Federal Constitution, which erased the traces of the military dictatorship and restored democracy in the country